2021
DOI: 10.4081/gc.2021.9635
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and risk of mortality and hospitalization in nursing home residents affected by COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) is a widespread condition in nursing homes (NHs). However, no research was made regarding frailty in NH residents during COVID-19 pandemic. The aim of this study was to assess whether frailty, assessed by the multidimensional prognostic index (MPI), can predict mortality/hospitalization in COVID-19 NH residents. A Cox’s regression analysis was used, reporting the results as hazard ratios (HRs) with 95% confidence intervals (CIs). 1146 NH residents affected by COVID-19 were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
1
5
1
Order By: Relevance
“…In the UK, 907 cases of SARS-CoV-2 infection were recorded in 189 care homes leading to a 48% lethality rate [ 1 ]. In the present study, infection lethality was significantly lower during the second wave of the pandemic, reaching 23.4% ( p < 0.001), similar to what was observed in a sample of Italian NHs in Veneto region and in a large sample of US NHs [ 13 , 33 ]. The fall in NH COVID-19 deaths reported in our study is consistent with a recent study by Ioannidis et al, describing a significant reduction in NH mortality rates in the second vs the first wave in 8 countries [ 21 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the UK, 907 cases of SARS-CoV-2 infection were recorded in 189 care homes leading to a 48% lethality rate [ 1 ]. In the present study, infection lethality was significantly lower during the second wave of the pandemic, reaching 23.4% ( p < 0.001), similar to what was observed in a sample of Italian NHs in Veneto region and in a large sample of US NHs [ 13 , 33 ]. The fall in NH COVID-19 deaths reported in our study is consistent with a recent study by Ioannidis et al, describing a significant reduction in NH mortality rates in the second vs the first wave in 8 countries [ 21 ].…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, during the first wave, more than half of SARS-CoV-2-positive residents were admitted to acute and intermediate care hospitals, while only one in ten was hospitalized during the second wave of the pandemic. The hospitalization rate observed during the second wave was much lower than that described by previous studies, reporting that about 20% of SARS-CoV-2-positive NH residents have been admitted to hospital during COVID-19 disease, with rates up to 45% among severely symptomatic cases, both in large US studies as well as in Italian samples [ 7 , 13 , 33 ]. The results we observed can be explained by the progressive upgrading of COVID-19 “bubbles” to create on-site IC units, where SARS-CoV-2 infected patients could be isolated from the negative ones while receiving appropriate multidisciplinary care, thus avoiding the need for hospitalization.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Finally, MPI has already been used as a prognostic factor in settings other than ICFs during the COVID-19 epidemic. In particular, in nursing home residents, we have shown that higher MPI values indicate a higher risk of mortality, independently of the presence or not of COVID-19 and vice versa (i.e., COVID-19 increases the risk of mortality independently of MPI values) [13]. More recently, we have reported that in older patients hospitalized for COVID-19, MPI is useful for better stratifying the risk of mortality, whilst more data are needed for predicting the risk of ICU admission [25].…”
Section: Discussionmentioning
confidence: 78%
“…A version of the MPI, modified from the original version that originally included information regarding nutritional status, disability, number of medications, risk of pressure sores, severity of comorbidities, social aspects [4] and using tests commonly used for the admission to the ICFs, was used [12,13]. This tool requires about 15-20 min for trained health professionals [12].…”
Section: Exposure: the Multidimensional Prognostic Index (Mpi)mentioning
confidence: 99%